EKSPLOITASI PEKERJA PADA INDUSTRI BATIK RUMAHAN - Muhammad Alhada Fuadilah Habib; Cut Rizka Al Usrah; Mukhammad Fatkhullah; Kanita Khoirun Nisa; Ayla Karina Budita (Social Welfare Study Program, 2022)
Abstract. Batik industry is one of the leading industries in Indonesia. Since UNESCO declared batik as one of the cultural treasures and identity of the Indonesian nation, batik production has increased in line with increasing market demand. One of the rapidly growing batik industries in Indonesia is the batik industry located in Lawean Village, Solo, Central Java. The industry uses a putting out system where batik workers do their work in their respective house production. Through this system, business owners no longer need to compile an environmental impact analysis, provide social security for workers, pay overtime, work space, and work equipment. However, this putting out system creates many problems, from environmental pollution, deprivation of social rights for workers, to exploitation of workers by business owners. This study aims to reveal forms of injustice to workers in the home batik industry, Lawean, Solo, Central Java through a constructivism (critical) approach. Primary data obtained through in-depth interviews on 14 research subjects and also supported by secondary data from previous studies. Determination of informants is done by using the snowball technique. The theory used in this study is the theory of power relations by Michael Foucault. The dominance of power that leads to injustice (exploitation), cannot be separated from the presence of persuasive power (the owner of the batik business who controls the workers) in the midst of the Lawean Batik Industry. This dominance of power occurs because of the inequality of intelligence and mastery of information technology between batik business owners and workers. Batik business owners have access/network to sell batik products both domestically and abroad, while workers do not have access/network to sell batik they produce directly. On the other hand, the